Odpowiedź :
Wzór funkcji kwadratowej
Etap 1.
[tex]\frac{x_1}{x_2}+\frac{x_2}{x_1}=\frac{x_1^2+x_2^2}{x_1 x_2}=\frac{(x_1+x_2)^2-2x_1x_2}{x_1 x_2}[/tex]
Etap 2.
[tex]\frac{(x_1+x_2)^2-2x_1x_2}{x_1 x_2}=\frac{(x_1+x_2)^2-2\cdot(-5)}{-5}=-2\frac{1}{20}[/tex]
[tex]\frac{(x_1+x_2)^2+10}{-5}=-\frac{41}{20}\ \ \ |\cdot(-20)[/tex]
[tex]4[(x_1+x_2)^2+10]=41[/tex]
[tex]4(x_1+x_2)^2+40=41[/tex]
[tex]4(x_1+x_2)^2=41-40[/tex]
[tex]4(x_1+x_2)^2=1\ \ \ |:4[/tex]
[tex](x_1+x_2)^2=\frac{1}{4}[/tex]
[tex]x_1+x_2=\sqrt{\frac{1}{4}}\ \ \ lub\ \ \ x_1+x_2=-\sqrt{\frac{1}{4}}[/tex]
[tex]x_1+x_2=\frac{1}{2}\ \ \ \ \ \ \ \ \ \ \ x_1+x_2=-\frac{1}{2}[/tex]
Etap 3.
[tex]x_{1}+x_{2}=-\frac{b}{a}=\frac{1}{2}[/tex]
[tex]b=-\frac{1}{2}a[/tex]
lub
[tex]x_{1}+x_{2}=-\frac{b}{a}=-\frac{1}{2}[/tex]
[tex]b=\frac{1}{2}a[/tex]
[tex]x_{1}\cdot x_{2}=\frac{c}{a}=-5[/tex]
[tex]c=-5a[/tex]
Wzór funkcji:
[tex]y=ax^2-\frac{1}{2}ax-5a[/tex]
lub
[tex]y=ax^2+\frac{1}{2}ax-5a[/tex]
Etap 4.
[tex](-2, 4)[/tex]
[tex]a\cdot(-2)^2-\frac{1}{2}a\cdot(-2)-5a=4[/tex]
[tex]4a+a-5a=4[/tex]
[tex]0=4[/tex]
Równanie sprzeczne.
lub
[tex]a\cdot(-2)^2+\frac{1}{2}a\cdot(-2)-5a=4[/tex]
[tex]4a-a-5a=4[/tex]
[tex]-2a=4\ \ \ \ |:(-2)[/tex]
[tex]a=-2[/tex]
Wzór:
[tex]y=ax^2+\frac{1}{2}ax-5a[/tex]
[tex]y=-2x^2+\frac{1}{2}\cdot(-2)x-5\cdot(-2)[/tex]
[tex]\underline{y=-2x^2-x+10}[/tex]